2013
DOI: 10.1002/pbc.24745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of latino and non-Latino patients with Ewing sarcoma

Abstract: Background Ewing sarcoma (ES) is a malignancy of bone and soft tissue in children and adults. Previous registry-based studies indicate that Latino patients with ES have inferior outcomes compared to non-Latino patients, though an etiology for this difference could not be identified. To explore possible differences that might underlie this disparity, we conducted a retrospective study to compare clinical characteristics, tumor features, healthcare access, and treatment outcomes between Latino and non-Latino pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Significant advancements over the last several decades have resulted in dramatic improvements in long‐term outcomes in children with cancer . However, the majority of studies suggest poorer survival among children from racial and ethnic minority groups . Among the populations experiencing poorer outcomes are Hispanics, the fastest growing ethnic minority group in the United States .…”
Section: Introductionmentioning
confidence: 99%
“…Significant advancements over the last several decades have resulted in dramatic improvements in long‐term outcomes in children with cancer . However, the majority of studies suggest poorer survival among children from racial and ethnic minority groups . Among the populations experiencing poorer outcomes are Hispanics, the fastest growing ethnic minority group in the United States .…”
Section: Introductionmentioning
confidence: 99%
“…This study did not find race or ethnicity to be associated with early death risk. Several studies have shown an impact of socioeconomic status on diagnosis and outcomes in pediatric cancer, [4][5][6][7][8][9][10] a topic summarized in a recent systematic review 11 ; however, its relationship with risk for early death was not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Latino patients have been found to be diagnosed with Ewing sarcoma at younger age compared to non-Latino patients in both children and adults. 17 However, social and cultural barriers often lead to a disproportionate number of such minorities experiencing lower SES and impaired access to health care, and these studies also found evidence of these factors. Additionally, insurance status is associated with survival disparities, where uninsured and Medicaid patients are more likely to present with advanced stage cancer.…”
mentioning
confidence: 88%